"Necropolítica e biopolítica na gestão da pandemia de Covid-19 no Brasil: uma análise crítica da atuação do governo Bolsonaro" - ALMEIDA, Louise Millany Lessa Oliveira de (2024)
This work aims to analyze how the Bolsonaro administration's management during the Covid-19 pandemic actively contributed to mass deaths through biopolitical mechanisms of discourse production and normativity, and how planned omission allowed preventable deaths to occur, guided by neoliberal interests. Using the theoretical frameworks of Michel Foucault and Achille Mbembe, this study seeks to highlight the intensification of necropolitical governmentality during the pandemic. In the first chapter, I develop the concept of Biopolitics in Foucault, followed by Mbembe's concept of Necropolitics to understand the intersection between the power of death, racism, and neoliberalism. Finally, in the last chapter, I draw on the evidence presented in the CPI's Pandemic Report to demonstrate the "making die and letting die" of the Bolsonaro government.